FULFILLMENT OF AUDIENCE NEEDS AND SATISFACTION ON THE GADGETIN YOUTUBE CHANNEL (NETNOGRAPHIC ANALYSIS) - Medeline Grace A. Rahawarin; Chontina Siahaan (Sociae Polites, 2026)
One of the most popular digital platforms is YouTube. YouTube plays an important role as a primary source for people in obtaining information and entertainment. One of the YouTube channels that discusses technology-related content is GadgetIn. This channel is known for presenting reviews of technology products such as smartphones, laptops, and other electronic devices. GadgetIn’s content creates dynamic interactions, where audiences not only watch the videos but also actively leave comments. Through the comment section, audience engagement can be seen, reflecting their needs and satisfaction toward GadgetIn’s content. This study aims to explain how GadgetIn’s YouTube content fulfills audience needs and satisfaction. This research uses a qualitative approach with a netnographic method by Kozinets and applies the Uses and Gratifications theory by examining the five types of audience needs. The results show that audiences actively use GadgetIn’s content to fulfill informational needs, entertainment needs, personal integrative needs, and social integrative needs through smartphone review content. The fulfillment of these needs then creates satisfaction for the audience after accessing GadgetIn’s content. Keywords: Audience Needs and Satisfaction, GadgetIn, Uses and Gratifications, YouTube